KETERKAITAN RUANG TERBUKA HIJAU DENGAN KEBUTUHAN OKSIGEN DI KOTA MANADO - Orlando Suryadinata; Martina A. Langi; Euis F. Pangemanan (COCOS, 2019)
ABSTRACT Increasing population growth has resulted in the development of cities as centers of activity demanded to accommodate community needs. The physical development of cities is often inseparable from changing the natural landscape and spatial planning resulting in a decrease in carrying capacity and environmental services. Land limitations and spatial planning are increasingly becoming important steps to improve environmental quality, one of its efforts is by building green open spaces. Based on the results of previous studies, this study aims to determine the possibility of increasing the need for an area of green open space in the city of Manado in 2020. The results showed that the need for Green Open Space (RTH) in the city of Manado experienced an increase in 2020 to 9,364.82 ha. Keywords: green open space, oxygen demand, Manado City